Geologic Control and Nitrate Levels of Springs Around Lake Havasu, Mohave and Lapaz Counties, Arizona, and San Bernardino County, CA - Wilson, Doyle C. (Arizona-Nevada Academy of Science, 2005)
From the Proceedings of the 2005 Meetings of the Hydrology Section - Arizona-Nevada Academy of Science - April 9, 2005, University of Nevada, Las Vegas